De flittige tobaksfabrikører: Henning Struck og Jens Pallesen Obel (1724-1814) - Tønnesen, Eva (Historisk Årbog for Roskilde Amt, 2019)
De flittige tobaksfabrikører: Henning Struck og Jens Pallesen Obel (1724-1814)